Treatment with Entinostat Heals Experimental Cholera by Affecting Physical and Chemical Barrier Functions of Intestinal Epithelia - Sarker, Protim (Antimicrob Agents Chemother, 2017)
We have shown previously that oral treatment with sodium butyrate or phenylbutyrate in an experimental model of shigellosis improves clinical outcomes and induces the expression of the antimicrobial peptide CAP-18 in the large intestinal epithelia. In a subsequent study, we found that entinostat, an aroylated phenylenediamine compound, has similar therapeutic potential against shigellosis. In this study, we aimed to evaluate entinostat as a potential candidate for host-directed therapy against cholera in an experimental model. Vibrio cholerae-infected rabbits were treated with two different dose regimens of entinostat: either 0.5 mg twice daily for 2 days or 1 mg once daily for 2 days. The effects of treatment on clinical outcomes and V. cholerae shedding (CFU count in stool) were observed. Immunohistochemical analysis was carried out to assess CAP-18 expression in ileal and jejunal mucosae. The serum zonulin level was measured by an enzyme-linked immunosorbent assay (ELISA) to evaluate gut permeability. Infection of rabbits with V. cholerae downregulated CAP-18 expression in the ileal epithelium; the expression was replenished by oral treatment with entinostat at either dose regimen. The level of zonulin, a marker of gut permeability, in serum was upregulated after infection, and this upregulation was counteracted after treatment with entinostat. Entinostat treatment also led to recovery from cholera and a decline in the V. cholerae count in stool. In conclusion, the improved clinical outcome of cholera for rabbits treated with entinostat is associated with the induction of CAP-18 and the reduction of gut epithelial permeability.